Lupin causes maize to increase organic acid exudation and phosphorus concentration in intercropping. Issue 3 (29th July 2022) - Schwerdtner, Ulrike; Lacher, Ulrike; Spohn, Marie
Abstract: Purpose: There is a need to develop agricultural practices that mobilize sparingly soluble soil phosphorus (P) due to increasing scarcity of P fertilizer. Interactions of different plant species in the rhizosphere might increase P mobilization, but the underlying mechanisms are still not fully understood. Methods: We conducted a pilot study with four plant species (maize, soy, lupin, mustard) grown alone and in combination with maize (intercropping) to investigate how species interact to mobilize P from iron phosphate (FePO4 ). Root exudates of individual plants were collected and analyzed for low molecular weight organic acid anions (LMWOA) and pH. Results: Maize increased its exudation of LMWOA and its biomass P concentration in intercropping, especially when grown together with lupin. This is the first study to show unequivocally that a high LMWOA concentration in the rhizosphere in intercropping is not only caused by high LMWOA release of the companion but also by an increased LMWOA exudation of the main crop. The high release of LMWOA was associated with a higher maize P concentration, indicating that enhanced LMWOA release in intercropping is beneficial for P acquisition of maize. Moreover, lupin and mustard mobilized more P from FePO4 than maize and soy likely through high LMWOA exudation (lupin) and rhizosphere alkalinization (mustard). Conclusion: Taken together, we reveal that intercropping with lupin increases the release of LMWOA by maize and concurrently the maize P concentration, suggesting that intercropping is useful for the mobilization of P from FePO4 because it affects the exudation of maize.